SethantÅ¡o sa Sesotho and Sesuto–English Dictionary: A Comparative Analysis of their Designs and Entries - Motjope-Mokhali, T.L.; Kosch, I.M.; Mafela, Munzhedzi James (Lexikos, 2020)
This article seeks to establish the relationship and extent of similarity between two Sesotho dictionaries, published in the 1800s and 2005 respectively. The two dictionaries under discussion are the Sesuto–English Dictionary by Mabille and Dieterlen and SethantÅ¡o sa Sesotho by Hlalele. The former dictionary, like most dictionaries of other African languages pioneered by the missionaries, is bilingual. The latter dictionary is the first monolingual dictionary for Sesotho and it was compiled by a mother tongue-speaker of the language. The closeness of the content of the two dictionaries is established by applying the user-perspective approach as the framework of analysis. Through an analysis of the designs and entries in the two dictionaries, the study discovers similarities and differences in terms of the use of non-standard symbols and atypical sound patterning, illustrative phrases/sentences and obsolete or archaic words. Given the amount of obsolete items in SethantÅ¡o sa Sesotho, one of the recommendations emanating from this study is that SethantÅ¡o sa Sesotho be revised or that a new monolingual dictionary be produced which will include more modern words that will meet the needs of contemporary users.